Implementação da Manufatura Enxuta em empresas de diferentes portes e setores: características, similaridades e diferenças - Rufino, Bruno Almeida (2019)
With the increase in competitiveness among companies, it becomes more evident the need to adopt production management systems that help eliminate waste, increase productivity in processes and, consequently, increase revenues and profits of organizations. In this context, Lean Manufacturing is gaining strength as, through the lean concept, it eliminates productive waste by increasing productivity, achieving significant results in organizations that apply it in their entirety. According to the literature on the subject, there is a shortage of comparative studies of the application of Lean Manufacturing in companies of different sizes and sectors. The present paper seeks to fill this gap in the literature, where the main object is to study how the implementation of Lean Manufacturing occurs in companies of different sizes and sectors, in order to identify which are the characteristics, similarities and differences of the implementation process. To carry out the study, the case study method is used, since it is an empirical research, where three field studies are carried out, each of them being in a different sector and size company. The information was collected through semi- structured interviews with employees with different functions in each organization. As a result of the study, it was possible to verify that, although the Lean Manufacturing presents universal concepts, practices and tools, its application and implementation can present peculiarities depending on the sector or size of the company, which does not interfere in the desired result, similarities are evidenced in the applied tools and the difficulty with behavioral issues and aspects that refer to the discipline of the people. The great asset of Lean culture is the understanding of the concepts behind the methodology, as well as the discipline and cultural and behavioral change that involves it.